TOWARD THE FUTURE OF ACCOUNTING INFORMATION SYSTEMS: A BIBLIOMETRIC EXPLORATION - Carolina, Yenni; Rapina, Rapina; Kenisah, Melania Lintang (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
Research on Accounting Information Systems (AIS) has expanded steadily since the 1970s. This study offers the most comprehensive and up-to-date mapping of the AIS knowledge base by analyzing 1,101 Scopus-indexed articles from 523 sources (1975–2023) using an integrated bibliometric approach with Biblioshiny (bibliometrix) and VOSviewer. Unlike prior reviews that relied on shorter time spans, single databases, or a single analytical tool, this study provides novel contributions by employing a longer historical window, triangulating multiple bibliometric software, and integrating intellectual, social, and conceptual structures within a unified framework. The analysis identifies prolific and influential authors, documents, and journals; maps collaboration patterns; and visualizes keyword co-occurrence, thematic evolution, and emerging research fronts. Publication output accelerated sharply after 2008 and peaked around 2020, while current work is increasingly shaped by technology-centric themes such as enterprise resource planning (ERP), big data, blockchain, artificial intelligence, and cloud computing. Indonesian scholars rank among the most productive contributors, yet cross-border collaboration remains concentrated in U.S.-anchored networks. For scholars, the periodized thematic maps and trending clusters (e.g., blockchain, AI, sustainable development) provide a reproducible roadmap for future inquiry, grant proposals, and curriculum development. For practitioners and policy makers, including accounting educators, professional bodies, and firms undergoing digital transformation, these findings highlight under-explored links between AIS design and organizational performance, guiding investment decisions and collaborative strategies. This study advances AIS research and strengthens its relevance for academic, professional, and regulatory communities confronting rapid technological and institutional change by consolidating historical milestones and surfacing forward-looking opportunities.